A review on fabric bagging: the concept and measurement methods. Issue 4 (3rd April 2018) - Sülar, Vildan; Seki, Yasemin
Abstract: Fabric bagging is a three-dimensional permanent deformation which can deteriorate aesthetical appearance and mechanical properties of garments. This review presents a brief look at the concept of bagging deformation consisting basic definitions, theories and modelling, objective and subjective evaluation and the parameters affecting fabric bagging. The effects of both fabric structural properties and bagging test parameters have been also explored. A thorough knowledge of bagging measurement by different laboratory tests such as unidirectional tensile, bursting strength, ball penetration tests and devices resembling an arm having an elbow point for simulating human movements in static or dynamic conditions was reviewed in details.